1993
DOI: 10.1029/93ja01013
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric response to solar wind dynamic pressure variations: Interaction of interplanetary tangential discontinuities with the bow shock

Abstract: Some magnetic impulse events observed in the polar region are related to vortices associated with plasma convection in the ionosphere. Recent analyses of satellite and ground data suggest that the interaction of solar wind dynamic pressure pulses and the magnetosphere may lead to the formation of velocity vortices in the magnetopause boundary layer region. This can in turn lead to the presence of vortices in the polar ionosphere. However, before reaching the Earth's magnetopause, these interplanetary pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 41 publications
6
64
0
Order By: Relevance
“…As a matter of fact, such approximation does not permit to take properly into account the magnetopause motion due to the interaction with the IS. In fact, Grib et al (1979) and Wu et al (1993) have found that the IS impact upon the magnetopause produces a rarefaction wave rather than a RFS. However, we note that our local model gives, into the magnetosheath, results close to those obtained by Samsonov et al (2007) (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, such approximation does not permit to take properly into account the magnetopause motion due to the interaction with the IS. In fact, Grib et al (1979) and Wu et al (1993) have found that the IS impact upon the magnetopause produces a rarefaction wave rather than a RFS. However, we note that our local model gives, into the magnetosheath, results close to those obtained by Samsonov et al (2007) (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that the change of the dynamic pressure within the transition region may be very complicated, and the dynamic pressures are relatively quiet in the adjacent upstream and downstream regions. Sudden changes in magnetic field together with jumps in plasma parameters such as the ion flux or the dynamic pressure are often associated with MHD discontinuities including tangential discontinuities, rotational discontinuities with anisotropic thermal pressure, and shocks (e.g., Saka & Kitamura 1976;Wu et al 1993;Dalin et al 2002;Riazantseva et al 2005Riazantseva et al , 2007Neugebauer 2006). Some identified DPPs can be classified into these types of discontinuities.…”
Section: Three-step Detection Algorithmmentioning
confidence: 99%
“…When the upstream conditions are not in a steady state, the interaction of the solar wind variations with the bow shock will further complicate the picture [Wu et al, 1993;Yan and Lee, 1994;Lin et al, 1996]. In theory the collision of a solar wind discontinuity with the bow shock creates seven discontinuities: a pair of shocks for each of fast, intermediate, and slow modes, plus a contact discontinuity.…”
Section: Theoretical Magnetosheath Modelsmentioning
confidence: 99%